RESPONSE OF PEANUT PLANTS (Arachis hypogaea L.) TO THE APPLICATION OF BOKASHI FERTILIZER BASED ON SECONDARY VEGETATION BIOMASS AND PHOSPHORUS ON MARGINAL LAND - Amelia Hasanah; Nini Mila Rahni; Fransiscus Suramas Rembon (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Peanuts (Arachis hypogeae L.) currently have low production levels due to the availability of fertile land. Bokashi fertilizer based on secondary vegetation biomass and phosphorus fertilizer can be used as a practical and environmentally friendly approach to maintain peanut plant growth and yield. This study aims to examine the interaction or independent treatment of bokashi fertilizer and phosphorus fertilizer on the growth and yield of peanut plants on marginal land. This study used a randomized block design with two factors. The first factor was bokashi fertilizer, consisting of 4 levels, namely without bokashi fertilizer (B0), 4 t ha-1 of bokashi fertilizer (B1), 8 t ha-1 of bokashi fertilizer (B2), and 12 t ha-1 of bokashi fertilizer (B3). The second factor is phosphorus fertilizer, consisting of 4 levels namely, no phosphorus fertilizer (F0), 100 kg ha-1 phosphorus fertilizer (F1), 125 kg ha-1 phosphorus fertilizer (F2) and 150 kg ha-1 phosphorus fertilizer (F3), resulting in 16 treatment combinations with 3 replicates. The results showed that the interaction between bokashi fertilizer and phosphorus fertilizer could enhance the growth and yield of groundnuts, particularly in terms of relative growth rate, leaf area index, net assimilation rate at 21-28 and 35-42 days after sowing, root-to-shoot ratio, chlorophyll content, number of pods, number of seeds, seed weight, 100-seed weight, and yield per hectare. The interaction treatment of bokashi fertilizer at a dose of 12 t ha-1 and phosphorus fertilizer at 150 kg ha-1 was the best treatment for peanut plant growth and yield.